Hubungan antara Sistem Manajemen Mutu Pendidikan dengan Peningkatan Prestasi Akademik Siswa: Penelitian - Halimatus Sakdiyah (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to determine the relationship between the Educational Quality Management System (EQMS) and the improvement of students’ academic achievement in secondary schools. The research employed a quantitative approach with a correlational method. Data were collected through a closed-ended questionnaire administered to 120 respondents, consisting of teachers and students from four public schools. Data analysis was conducted using the Pearson Product Moment correlation test and simple linear regression to measure the strength of the relationship between variables. The results showed a positive and significant relationship between EQMS and students’ academic achievement, with a correlation coefficient of r = 0.731 and a coefficient of determination R² = 0.534. This indicates that approximately 53.4% of the variation in academic achievement can be explained by the implementation of EQMS, particularly in leadership, quality planning, and continuous evaluation aspects. The findings confirm that the better the implementation of quality management systems in schools, the higher the academic achievement attained by students. This study implies that strengthening quality management systems through effective leadership and a strong quality culture is essential for improving the overall quality of education in Indonesia.